Valutazione clinica e metabolica dell’impiego dell’insulina Lispro in pazienti con diabete mellito scompensato - Uneddu, Antonio; Paolini, Tito Antonio (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
The aim of the present work is to report preliminary results about the administration of an insulin analogue, LisPro, to treat diabetic chetoacidosis. This new procedure, in respect to insulin continuous infusion, allow significant cost reduction in terms of medical and nurses time dedicated to the patient and hospitalization length. In our experience, LisPro treatment compared to the standard of care, has allowed hospital time reduction of 2,1 days per patient. This can be translated in cost saving of about 700,00 euro per case. These preliminary data, replicating the results coming from published international experiences, have to be confirmed in our country through the implementation of more representative studies